Macrosolen Globosus (Roxb.) Tiegh. (loranthaceae): A New Addition of a Mistletoe Species to the Flora Of Odisha, India - Mishra, Sweta; Kumar N, Sanath; Rath, Sakti Kanta; Kumar, Sanjeet (Indian Forester, 2024)
No Abstract.